Synthesis of Symmetrical and Non‐Symmetrical Bivalent Neurotransmitter Ligands. Issue 3 (8th March 2016) - Stuhr‐Hansen , Nicolai; Andersen, Jacob; Thygesen, Mikkel B.; Strømgaard, Kristian
Abstract: A novel procedure for synthesis of bivalent neurotransmitter ligands was developed by reacting O ‐benzyl protected N ‐nosylated dopamine and serotonin with alkyl‐ or PEG‐linked diols under Fukuyama‐Mitsunobu conditions in the presence of DIAD/PPh3 generating three different bivalent neurotransmitter ligands in a one‐pot reaction. The methodology establishes a facile route towards bivalent neurotransmitter ligands, and libraries of in total 40 symmetrical and non‐symmetrical bivalent and monovalent dopamine and serotonin compounds linked through alkyl or PEG spacers of varying length were prepared. Interestingly, attempted synthesis of an O ‐ tert ‐butyl analogue of the N ‐nosylated serotonin precursor resulted in unexpected tert‐ butylations at the 1‐, 2‐ and 6‐positions of the indole skeleton. We found that upscaling of selected bivalent serotonin ligands was most efficiently performed via N, O ‐bis‐nosyl‐serotonin since global de‐nosylation was carried out as a final step after Fukuyama‐Mitsunobu dimerization. Abstract : A facile route towards bivalent neurotransmitter ligands, and libraries of in total 40 symmetrical and non‐symmetrical bivalent and monovalent dopamine and serotonin compounds linked through alkyl or PEG spacers of varying length have been prepared via Fukuyama‐Mitsunobu chemistry.